Efektivitas Penggunaan E-Modul Berbasis Case Method Terhadap Kemampuan Berpikir Kritis - Nita Sofia; Hendrik Heri Sandi; Irdha Yusra; Mentari Ritonga (Universitas Negeri Padang, 2023)
The research aims to analyze the effectiveness of using case method-based e-modules on students' critical thinking abilities in Income Tax Management courses. This research is a quasi-experimental research with a pretest-posttest control group research design. The sample for this research consisted of students from the Tax Management Study Program who were enrolled in two Income Tax Management classes, with a total of 54 students. This research was conducted at the Faculty of Economics, Padang State University. The learning model used is the Case Method using the Case Method-based Tax E-Module media, which has been developed previously. The research results show that the use of the case method-based taxation e-module is effective in improving students' critical thinking skills.